(untitled) (Research, Society and Development, 2020)
The quality of meat related to sensory parameters is widely observed by the end consumer, where the public becomes increasingly demanding. In order to obtain such a product, the industry uses various means, including the use of antibiotic that promotes growth. However, Brazil is the largest exporter of broiler chickens, making it adapt to legislative requirements, which in turn has been restricting and prohibiting the use of growth-promoting antibiotics, justified by the emergence of resistance cross. The addition of essential oil to the animal diet can help by acting as antimicrobials and antioxidants, performing actions similar to the growth-promoting antibiotic, and therefore become a possible substitute for this compound. Thus, the objective of this study is to evaluate the moisture content, ash, protein, lipids, pH, loss from cooking, shear strength and color in chicken breast cuts that were subjected to different diets based on corn and bran soybean with the addition of growth promoting antibiotic and essential oil in different concentrations (0; 0.05; 0.10; 0.15 kg / ton of feed). All methodologies were carried out through laboratory research of a quantitative nature. Satisfactory results were obtained for all physical and physical-chemical parameters when compared to the literature, in addition to showing that the addition of the essential oil of oregano and cinnamon, in a concentration of 0.10 kg / ton of feed, presented similar results when compared meat cuts from treatment with the use of growth-promoting antibiotic, enabling new studies for replacement in the national production chain.